SIGNIFIKANSI KONSEP KELAHIRAN KEMBALI MENURUT INJIL YOHANES 3 : 1 – 13, IMPLIKASI BAGI GEREJA MASA KINI - Sanjay Nadeak (JURNAL IMPARTA, 2022)
The Gospel of John emphasizes God's sovereignty in His plan of salvation. More than the Synoptic Gospels, it emphasizes that no one can be saved without being drawn by the Holy Spirit. There are many passages in John's Gospel that emphasize the importance of salvation, because one cannot be saved without being drawn first to Christ by the Father. The new birth also uses the verb to be begotten (John 1:12-13), Likewise, humans cannot do any good to be begotten again to be a child of God. This phrase is full of the theme of grace. There is no denying that there is a strong emphasis on God's sovereign will, but for John, that does not make grace irresistible, nor does it deny the freedom of human will. Faith is a gift from God, because without the influence of the Holy Spirit who draws us in, we cannot hear and believe. This study uses qualitative research with a literature review approach, thus strengthening the results of this study